Knowledge and practice of universal precautions among nursing staff at a tertiary care hospital in South Gujarat, India - Solanky, Priti; Baria, Hinal; Nerulkar, Alka; Chavda, Nilesh (International Journal Of Community Medicine And Public Health, 2016)
Background: Health care providers are at an increased risk of exposure to various infections like HIV, Hepatitis B, Hepatitis C etc. These infections are prevented if proper universal precautions are observed by health care providers consistently in their day to day clinical work. In study we have explored knowledge and practice of universal precautions among nursing staff. Methods: A cross sectional study carried out among staff nurses in December 2013. Self-administered semi structured proforma was used for data collection. Information regarding knowledge and practice of universal precautions was collected. Results: Out of 88 participants interviewed, almost all of them reported of having awareness about universal precautions and personal protective equipments. Only 44.3% nurses mentioned all the correct measures for universal precautions. 89.77% nurses were aware about health hazards of needle stick injury but only 67.05% correctly reported about how needle stick injury can be prevented. 38.64% nurses had experienced needle stick injury while working and most of them (79.41%) followed proper guidelines. Conclusions: correct knowledge regarding universal precautions among nursing staff is still not of satisfactory level and training at repeated interval needs to be given to ensure correct knowledge as well as implementation of universal precautions.